Multiresidue analysis of pesticides in water from rice cultures by on-line solid phase extraction followed by LC-DAD - Santos, TCR; Rocha, L. C.; Barcelo, D. (Gordon Breach Sci Publ Ltd, 1998)
An automated on-line solid phase extraction procedure followed by liquid chromatography with diode array detection was investigated for the determination of different classes of pesticides in water samples containing varied amount of humic substances. The different pesticides used were: carbendazin, carbofuran, atrazine, diuron, propanil, molinate, alachlor, parathion-ethyl, diazinon, trifluralin and the degradation products deisopropylatrazine and deethylatrazine. Humic substances extracted from a Brazilian sediment were used from 5 to 80 mg/l and their influence on recoveries was evaluated in neutral and acidic media. Recoveries higher than 70% were obtained for all the pesticides, from the preconcentration of 75 mi of aqueous sample fortified at 2 ng/ml using precolumns packed with PLRP-S. Good recoveries were obtained at neutral pH for most of the analytes up to 40 mg/l of humic acid. Only at 80 mg/l the recoveries were significantly affected, both at acidic and neutral pH. The method was applied to the determination of pesticides in river water spiked at 0.1 to 1 ng/ml. Detection limits obtained for water containing 10 mg/l of humic acid were between 0.05 and 0.3 ng/ml.
Keywords: pesticides; humic acids; water; solid phase extraction